2002
DOI: 10.1007/s11661-002-0330-z
|View full text |Cite
|
Sign up to set email alerts
|

Fatigue deformation-induced response in a superduplex stainless steel

Abstract: The cyclic deformation behavior of SAF 2507 superduplex stainless steel (SDSS) was studied under constant plastic-strain amplitudes. The cyclic hardening/softening curves show initial hardening, followed by softening and, finally, saturation behavior. Two regimes can be differentiated in the cyclic stress-strain curve (CSSC) of SDSS. The transition point at which the cyclic strain-hardening rate changes is identified to be p /2 ϭ 7 ϫ 10 Ϫ3 . Transmission electron microscopy (TEM) results on dislocation structu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 20 publications
(10 reference statements)
1
6
0
Order By: Relevance
“…The most recent study on the cyclic response of a duplex stainless steel (53 pct ␥-47 pct ␦) was conducted by Goh et al [17] They presented similar results to those of Vogt et al, i.e., two different regimes were identified in the CSSCs. They also found that at a plastic-strain amplitude below 7 ϫ 10 Ϫ3 , austenite mainly controls the cyclic deformation, whereas both phases take part in accommodating plastic strain.…”
Section: Introductionsupporting
confidence: 54%
See 1 more Smart Citation
“…The most recent study on the cyclic response of a duplex stainless steel (53 pct ␥-47 pct ␦) was conducted by Goh et al [17] They presented similar results to those of Vogt et al, i.e., two different regimes were identified in the CSSCs. They also found that at a plastic-strain amplitude below 7 ϫ 10 Ϫ3 , austenite mainly controls the cyclic deformation, whereas both phases take part in accommodating plastic strain.…”
Section: Introductionsupporting
confidence: 54%
“…Magnin et al [5,6] and Goh et al [17] have reported the same tendency to have two regimes in their CSSCs, changing from a high CSHR in the first regime to a low one in the second regime. Transition points were identified at pa values of 1 ϫ 10 Ϫ3 and 7 ϫ 10 Ϫ3 , respectively.…”
Section: Cyclic Stress-strain Responsementioning
confidence: 86%
“…Goh and Yip [71] conducted plastic strain controlled fatigue test ( ε pl /2 = 2 × 10 −4 to 8 × 10 −2 ) with SAF 2507 grade of DSS. They observed a common trend of cyclic hardening/softening for all the imposed values of ε pl /2.…”
Section: Specimensmentioning
confidence: 99%
“…Llanes et al [36] have described the cyclic stress-strain response of DSS in the annealed and aged conditions in three stages in terms of plastic strain amplitudes ( ε pl /2 < 10 −4 , 10 −4 < ε pl /2 < 10 −3 , ε pl /2 > 10 −3 ) each amenable to be characterized by well-defined and distinct cyclic deformation mechanisms. Goh and Yip [71] identified two separate regimes with different strain-hardening rates in the CSSC plotted by them. The first regime, at ε pl /2 < 7.0 × 10 −3 , had a high cyclic strain-hardening rate, while the second regime, at ε pl /2 > 7.0 × 10 −3 , had a strain-hardening rate that is less pronounced than the first.…”
Section: Cyclic Stress-strain Curvementioning
confidence: 99%
“…Moreover, the dislocation substructures and their patterns undergo changes during cyclic plastic deformation (Kuhlmann-Wilsdorf and Laird, 1977; Lukas and Kunz, 2002; Ma and Laird, 1988; Mayama et al., 2008; Mughrabi, 1983, 2006, 2009). It has already been investigated by many eminent scientists that cyclic plastic deformation alters the microstructure in different length scales and causes extreme instabilities with different loading amplitudes (Das et al., 2011b, 2011c; Goh and Yip, 2002; Shih et al., 2010; Yaguchi et al., 2001). Plastic deformation usually results in spatially heterogeneous arrangement/patterning of dislocations in the matrix.…”
Section: Introductionmentioning
confidence: 99%